O mestrado profissional na área de ensino de Ciências e Matemática: alguns esclarecimentos - Moreira, Marco; Nardi, Roberto [UNESP] (Universidade Tecnologica Federal do Parana (UTFPR), 2010)
This paper, elaborated from documents created and used in the last years by the commissions and coordinations of the Science and Mathematics Teaching CAPES/MEC (Coordination of Improvement of Higher Education Personnel/Ministry of Education) Area, brings some explanations regarding the professional master’s degree in Science and Mathematics Teaching. This kind of master’s program is an innovation in Brazil and may contribute significantly to the improvement of science and mathematics teaching in the country. It may also stimulate the development of similar proposals in other Latin-American countries.

Este artigo, elaborado a partir de documentos gerados e utilizados nos últimos anos pelas comissões e coordenações da Área de Ensino de Ciências e Matemática da CAPES (Coordenação de Aperfeiçoamento de Pessoal de Nível Superior)/MEC, contém alguns esclarecimentos relativos ao Mestrado Profissional em Ensino de Ciências e Matemática. Esse tipo de mestrado é uma inovação no Brasil e constitui-se em uma iniciativa promissora para a melhoria do ensino de Ciências e Matemática no país. Poderá também estimular o desenvolvimento de propostas em outros países que apresentam similaridades com a situação educacional brasileira.
Professional master degree in the field of Science and Mathematics Teaching:some clarifications
Keywords: Science and Mathematics Teaching; Graduate courses; Professional master’s degree; Ensino de Ciências e Matemática; Pós-graduação; Mestrado profissional